Polyester Shrink Film

By setting a specific impact strength and shrinkage ratio in the polyester-based shrinkage film, the lack of impact resistance and shrinkage uniformity of the polyester-based shrinkage film in the prior art is solved, and better automatic packaging and printing adaptability and shrinkage uniformity are achieved.

CN115551928BActive Publication Date: 2025-02-25C I TAKIRON CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202080100129.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-04-30
Publication Date
2025-02-25
Estimated Expiration
2040-04-30

AI Technical Summary

Technical Problem

The existing polyester-based shrink films have shortcomings in terms of impact resistance and uniformity of shrinkage near shrinkage temperature, resulting in poor adaptability of high-speed automatic packaging, poor printing adaptability, and large shrinkage deviation at temperatures near shrinkage temperature.

Method used

By preparing a polyester-based shrink film mainly composed of polyester resin, specific measures include setting a range of impact resistance A1 to 20 to 60 J/mm before shrinkage, a range of impact resistance A2/A1×100 after shrinkage, and a range of shrinkage B1/B2×100 to 70 to 90% to ensure the impact resistance and uniformity of the shrinkage film.

Benefits of technology

The excellent impact resistance of the polyester-based shrink film and the uniformity of the shrinkage rate near the shrinkage temperature are achieved, the adaptability of high-speed automatic packaging and printing is improved, and the shrinkage rate deviation near the shrinkage temperature is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115551928B_ABST
    Figure CN115551928B_ABST
Patent Text Reader

Abstract

The present invention provides a polyester shrink film having excellent impact resistance and uniform shrinkage near the shrinkage temperature. The polyester shrink film satisfies the following structures (a) to (c). (a) The impact strength before shrinkage measured by a film impact tester is defined as A1, which is 20 to 60 J / mm, (b) When the impact strength measured by a film impact tester after shrinking the polyester shrink film by 10% in warm water at 80°C is defined as A2, the value represented by A2 / A1×100 is 60 to 110%, (c) When the shrinkage under the conditions of 80°C and 10 seconds is defined as B1 and the shrinkage under the conditions of 90°C and 10 seconds is defined as B2, the value represented by B1 / B2×100 is 70 to 90%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polyester-based shrink film.

[0002] More specifically, the present invention relates to a polyester shrink film having excellent impact resistance and a uniform shrinkage rate near a shrinkage temperature. Background Art

[0003] Conventionally, polyethylene resins, polypropylene resins, polyvinyl chloride resins, polyester resins, etc. have been used as main components of shrink films in order to achieve labeling and decoration effects on various containers such as plastic bottles.

[0004] Furthermore, polyolefin-based shrink films mainly composed of polyethylene resin, polypropylene resin, etc. are preferably used because they are general-purpose products, are low-priced, and are easy to dispose of (for example, see Patent Document 1).

[0005] More specifically, a polyolefin-based multilayer shrink film is a multilayer structure of at least three layers having two surface layers containing a propylene-based resin and an inner layer containing a crystalline propylene resin or an ethylene-based resin polymerized using a metallocene catalyst, which is biaxially stretched under stretching conditions with an area stretching ratio of 20 times or more in a manner such that the transverse stretching ratio is greater than the longitudinal stretching ratio, and the following (a) to (e) are satisfied at the same time.

[0006] (a) The thickness is in the range of 6 to 11 μm.

[0007] (b) The tensile elastic modulus is 0.8 GPa or more.

[0008] (c) The heat shrinkage at 120°C is 35% or more.

[0009] (d) The shrinkage after storage in an atmosphere of 40°C for 7 days is 4% or less.

[0010] (e) The tear strength is 30 mN or more.

[0011] In addition, a polyester shrink film having high transparency, impact resistance, excellent low-temperature shrinkage, and biodegradability has been proposed (for example, see Patent Document 2).

[0012] That is, a shrink film is composed of a lactic acid polymer having a weight average molecular weight of 10,000 to 700,000, wherein the lactic acid polymer contains a structural unit obtained by dehydration condensation of lactic acid, a polyester structural unit obtained by dehydration condensation of a dicarboxylic acid and a diol, and / or a polyether polyester structural unit obtained by dehydration condensation of a dicarboxylic acid and a polyether polyol.

[0013] Furthermore, there is a polyester shrink film having a thickness of 10 to 120 μm, a 1% shrinkage starting temperature of 35 to 80° C., an impact strength of 6 kgf·cm or more in a film impact test, and a maximum shrinkage in a stretching direction of 35 to 90%.

[0014] Prior art literature

[0015] Patent Literature

[0016] Patent Document 1: Japanese Patent Application Publication No. 2011-126247 (claims, etc.)

[0017] Patent Document 2: Japanese Patent No. 3482743 (claims, etc.) Summary of the invention

[0018] However, the polyolefin-based shrink film described in Patent Document 1 has disadvantages such as a small value of elastic modulus, low heat resistance, and relatively poor transparency, although having a multilayer structure.

[0019] Therefore, there are problems in manufacturing such as poor suitability for high-speed automatic packaging and printing, and the decrease in tear strength makes it easy to cause damage from air vents provided by the automatic packaging machine.

[0020] In addition, the polyester shrink film containing a structural unit obtained by dehydration condensation of lactic acid described in Patent Document 2 has a problem of high production cost and economic disadvantage due to the use of a special polyester resin and the like.

[0021] In addition, it was found that the shrink film containing the structural unit derived from lactic acid has low mechanical strength and high water absorption, and therefore has a problem of large deviation in shrinkage rate due to differences in shrinkage temperature and crystallinity. In particular, it was found that there is a problem of large deviation in shrinkage rate at a temperature around the shrinkage temperature of about 100°C due to the relationship with water absorption.

[0022] Furthermore, conventional shrink films, including the polyester shrink film containing a structural unit obtained by dehydration condensation of lactic acid described in Patent Document 2, do not take into account the preferred ranges of impact strength before shrinkage, impact strength after shrinkage, and shrinkage rate near shrinkage temperature.

[0023] Therefore, the conventional shrink film has the problem that only a shrink film having poor impact resistance and large deviation in shrinkage near the shrinkage temperature can be obtained.

[0024] Therefore, the inventors of the present invention have found that, in the case where a structural unit derived from lactic acid is substantially not contained, a shrink film that shrinks uniformly and stably can be obtained by limiting the predetermined impact strength to a value within a predetermined range and limiting the ratio of the shrinkage rate near the shrinkage temperature, and have completed the present invention.

[0025] That is, an object of the present invention is to provide a shrinkage film or the like which has excellent impact resistance and is excellent in uniformity and stability of shrinkage ratio near the shrinkage temperature.

[0026] According to the present invention, there is provided a polyester shrink film derived from a polyester resin, which satisfies the following structures (a) to (c), thereby being able to solve the above-mentioned problems.

[0027] (a) The impact strength before shrinkage measured by a pendulum film impact tester is defined as A1, and this A1 is a value within a range of 20 to 60 J / mm.

[0028] (b) When the impact strength measured by a pendulum film impact tester after shrinking the polyester shrink film by 10% in hot water at 80°C is defined as A2, the value represented by A2 / A1×100 in relation to A1 is a value within the range of 60 to 110%.

[0029] (c) When the shrinkage ratio of the polyester shrink film when it is shrunk in warm water at 80°C for 10 seconds is defined as B1, and the shrinkage ratio of the polyester shrink film when it is shrunk in warm water at 90°C for 10 seconds is defined as B2, the value represented by B1 / B2×100 is a value within the range of 70 to 90%.

[0030] That is, by satisfying the configuration (a), it is possible to obtain, in the polyester shrink film before shrinkage, a favorable impact strength within a predetermined range of values ​​measured by a pendulum film impact tester.

[0031] In addition, by satisfying configuration (b), even when the impact strength values ​​of A1 and A2 slightly deviate, a predetermined ratio (A2 / A1×100) of good impact strength A1 and A2 can be obtained in the polyester shrink film that shrinks under predetermined conditions by reducing the elements of the predetermined influencing factors.

[0032] Furthermore, by satisfying configuration (c), even when there is a slight deviation in the A1 and A2 values ​​of the impact strength of configuration (a) and configuration (b), it is possible to reduce the elements of the prescribed influencing factors and obtain a prescribed ratio (B1 / B2×100) from a stable and uniform shrinkage rate near the shrinkage temperature of the polyester shrinkage film (for example, 80 to 90° C., and the same applies hereinafter).

[0033] Therefore, by limiting (A2 / A1×100) and (B1 / B2×100) to values ​​within the prescribed ranges, respectively, a shrinkage film having excellent impact resistance and excellent uniformity and stability of shrinkage ratio near the shrinkage temperature can be provided.

[0034] Furthermore, as described below, good results can be obtained in a predetermined drop test.

[0035] In the present invention, the impact strength A2 is preferably a value within the range of 20 to 45 J / mm.

[0036] By specifically limiting A2 of the impact resistance to a value within a predetermined range in this manner, it is easy to control the numerical value represented by A2 / A1×100 to a value within the predetermined range.

[0037] In the present invention, the shrinkage ratio B1 is preferably a value within a range of 35 to 80%, and the shrinkage ratio B2 is preferably a value within a range of 40 to 85%.

[0038] By specifically limiting the shrinkage ratio B1 and the shrinkage ratio B2 to values ​​within the prescribed range, respectively, it is easy to control the numerical value represented by B1 / B2×100 to a value within the prescribed range.

[0039] In the present invention, the film thickness before shrinkage is preferably a value within the range of 10 to 100 μm.

[0040] By specifically limiting the film thickness before shrinkage to a value within a predetermined range in this manner, it is easier to control the numerical value represented by A2 / A1×100, the numerical value represented by B1 / B2×100, and the like to be within the predetermined range.

[0041] In the present invention, the stretch ratio in the MD direction of the film before shrinkage is preferably a value within the range of 100 to 200%.

[0042] By specifically limiting the stretch ratio in the MD direction of the film before shrinkage to a value within a predetermined range, it is easy to more easily and quantitatively control the values ​​represented by A2 / A1×100 and B1 / B2×100 to values ​​within the predetermined range.

[0043] In the present invention, it is preferred that the stretch ratio in the TD direction of the film before shrinkage is a value within a range of 300 to 600%.

[0044] By specifically limiting the stretch ratios in both the MD direction and the TD direction of the film before shrinkage to values ​​within a specified range, it is easy to more easily and quantitatively control the values ​​represented by A2 / A1×100, the values ​​represented by B1 / B2×100, etc. to values ​​within the specified range.

[0045] In the present invention, the haze value of the film before shrinkage measured in accordance with JIS K 7105 is preferably 5% or less.

[0046] By specifically limiting the haze value to a value within a predetermined range in this manner, it is also easy to quantitatively control the transparency of the polyester shrinkage film.

[0047] In the present invention, the content of the amorphous polyester resin is preferably a value within a range of 90 to 100% by weight of the total amount of the resin.

[0048] By specifically limiting the content of the amorphous polyester resin in this way, it is easier to adjust the impact strength and the shrinkage rate near the shrinkage temperature to a desired range, and it is also easier to quantitatively control the haze value and the like.

[0049] In addition, the balance of the amorphous polyester resin in the total amount of the resin is a value contributed by the crystalline polyester resin and resins other than the polyester resin. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 (a) to (c) are diagrams for explaining different forms of the polyester shrink film.

[0051] Figure 2 This is a diagram for explaining the relationship between the impact strength (A1) of a polyester shrink film before shrinkage and the shrinkage ratio (B1) when shrinking under predetermined heating conditions (hot water 80° C., 10 seconds).

[0052] Figure 3 This is a diagram for explaining the relationship between the impact strength (A1) of a polyester shrink film before shrinkage and the shrinkage ratio (B2) when shrinking under predetermined heating conditions (hot water at 90° C. for 10 seconds).

[0053] Figure 4 This is a diagram for explaining the relationship between the impact strength (A2) of a polyester shrink film after shrinkage (warm water 80°C, 10%) and the shrinkage ratio (B1) under predetermined heating conditions (warm water 80°C, 10 seconds).

[0054] Figure 5 This is a diagram for explaining the relationship between the impact strength (A2) of a polyester shrink film after shrinkage (warm water 80°C, 10%) and the shrinkage ratio (B2) under predetermined heating conditions (warm water 90°C, 10 seconds).

[0055] Figure 6 This is a graph for explaining the relationship between the ratio of the impact strength (A2) after shrinkage (hot water 80°C, 10%) / the impact strength (A1) before shrinkage of a polyester shrink film and the shrinkage rate (B1) under predetermined heating conditions (hot water 80°C, 10 seconds).

[0056] Figure 7This is a graph for explaining the relationship between the ratio of the impact strength (A2) after shrinkage (hot water 80°C, 10%) / the impact strength (A1) before shrinkage of a polyester shrink film and the shrinkage rate (B2) under predetermined heating conditions (hot water 90°C, 10 seconds).

[0057] Figure 8 This is a graph for explaining the relationship between the ratio of the impact strength (A2) after shrinkage (warm water 80°C, 10%) / the impact strength (A1) before shrinkage of a polyester shrink film and the ratio of the shrinkage rate (B1) under a predetermined heating condition (warm water 80°C, 10 seconds) / the shrinkage rate (B2) under a predetermined heating condition (warm water 90°C, 10 seconds). DETAILED DESCRIPTION

[0058] [First embodiment]

[0059] The first embodiment is a polyester-based shrink film, characterized in that it is a polyester-based shrink film derived from a polyester resin and satisfies the following structures (a) to (c).

[0060] (a) The impact strength before shrinkage measured by a pendulum film impact tester is defined as A1, and this A1 is a value within a range of 20 to 60 J / mm.

[0061] (b) When the impact strength measured by a pendulum film impact tester after shrinking the polyester shrink film by 10% in hot water at 80°C is defined as A2, the value represented by A2 / A1×100 in relation to A1 is a value within the range of 60 to 110%.

[0062] (c) When the shrinkage rate of the polyester shrink film when shrinking under the conditions of hot water at 80°C for 10 seconds is set to B1, and the shrinkage rate of the polyester shrink film when shrinking under the conditions of hot water at 90°C for 10 seconds is set to B2, the value represented by B1 / B2×100 is a value within the range of 70 to 90%.

[0063] Hereinafter, various parameters and the like will be specifically described according to the configuration of the polyester shrink film of the first embodiment.

[0064] 1. Polyester resin

[0065] Basically, the type of polyester resin is not limited, and polyester resins composed of diol and dicarboxylic acid, polyester resins composed of diol and hydroxycarboxylic acid, polyester resins composed of diol, dicarboxylic acid and hydroxycarboxylic acid, or mixtures of these polyester resins are generally preferred.

[0066] Here, the diol as a compound component of the polyester resin may be at least one of aliphatic diols such as ethylene glycol, diethylene glycol, propylene glycol, butanediol, neopentyl glycol, hexanediol, etc., alicyclic diols such as 1,4-cyclohexanedimethanol, and aromatic diols.

[0067] Similarly, the dicarboxylic acid as the compound component of the polyester resin may include at least one of aliphatic dicarboxylic acids such as adipic acid, sebacic acid, and azelaic acid, aromatic dicarboxylic acids such as terephthalic acid, naphthalene dicarboxylic acid, and isophthalic acid, alicyclic dicarboxylic acids such as 1,4-cyclohexane dicarboxylic acid, and ester-forming derivatives thereof.

[0068] Similarly, as the hydroxycarboxylic acid as the compound component of the polyester resin, at least one of lactic acid, hydroxybutyric acid, polycaprolactone and the like can be mentioned.

[0069] In addition, as the amorphous polyester resin, for example, an amorphous polyester resin composed of a dicarboxylic acid and a diol can be preferably used, wherein at least 80 mol% of the dicarboxylic acid is composed of terephthalic acid, and the diol is composed of 50 to 80 mol% of ethylene glycol and 20 to 50 mol% of one or more diols selected from 1,4-cyclohexanedimethanol, neopentyl glycol and diethylene glycol. If necessary, other dicarboxylic acids and diols, or hydroxycarboxylic acids can be used to change the properties of the film. In addition, each can be used alone or as a mixture.

[0070] On the other hand, examples of the crystalline polyester resin include polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, polybutylene naphthalate, and polytrimethylene terephthalate, and these may be used alone or as a mixture.

[0071] When the polyester resin is a mixture of an amorphous polyester resin and a crystalline polyester resin, in order to obtain good heat resistance, shrinkage rate, etc., the blending amount of the amorphous polyester resin is preferably a value in the range of 90 to 100 weight %, and more preferably a value in the range of 91 to 100 weight % relative to the total amount of the resin constituting the polyester shrinkage film.

[0072] 2. Composition (a)

[0073] The configuration (a) is an essential configuration requirement, and its summary is that in the polyester shrink film of the first embodiment, the impact strength before shrinkage (sometimes referred to as A1) measured by a pendulum film impact tester is a value within the range of 20 to 60 J / mm.

[0074] The reason for this is that by setting the impact resistance before shrinkage to a value within a predetermined range, good impact resistance can be obtained in the polyester shrinkage film.

[0075] More specifically, if the impact strength (A1) before shrinkage is less than 20 J / mm, the mechanical strength may decrease, and the polyester shrink film may be poor in high-speed automatic packaging suitability, printing suitability, etc., or may be easily damaged by the exhaust pinholes provided by the automatic packaging machine.

[0076] On the other hand, if the impact strength (A1) before shrinkage is a value exceeding 60 J / mm, it may be difficult to obtain a good and uniform shrinkage ratio near the shrinkage temperature.

[0077] Therefore, in the configuration (a), the impact strength before shrinkage is more preferably a value within the range of 23 to 50 J / mm, and even more preferably a value within the range of 25 to 40 J / mm.

[0078] Here, Figure 2 and Figure 3 4 and 5 show the relationship between the impact strength (A1) of the polyester shrinkage film before shrinkage and the shrinkage ratio (B1, B2) of the polyester shrinkage film after heat treatment under predetermined conditions.

[0079] These Figure 2 and Figure 3 The measured data shown in the table all have considerable deviations, and it can be understood that the impact strength (A1) of the polyester shrinkage film before shrinkage and the shrinkage ratio (B1, B2) of the polyester shrinkage film after heat treatment under predetermined conditions are not sufficiently correlated.

[0080] in addition, Figure 4 and Figure 5 4 and 5 show the relationship between the impact strength (A2) of the polyester shrinkage film after shrinkage under predetermined conditions and the shrinkage ratio (B1, B2) of the polyester shrinkage film after heat treatment under predetermined conditions.

[0081] These Figure 4 and Figure 5 The data shown in the table all have considerable deviations, which indicates that the impact strength (A2) of the shrunk polyester shrink film and the shrinkage ratio (B1, B2) of the polyester shrink film heated under predetermined conditions are not sufficiently correlated.

[0082] In addition, the shrinkage rate of the polyester-based shrinkage film of the first embodiment is defined by the following formula.

[0083] Shrinkage (%) = (L 0 -L 1 ) / L 0 ×100

[0084] L 0 : Dimensions of the sample before heat treatment (long side or width direction)

[0085] L1 : Dimensions of the sample after heat treatment (with L 0 Same direction)

[0086] 3. Composition (b)

[0087] The component (b) is a necessary component, and its main point is that when the impact strength of the polyester shrinkage film of the first embodiment is set to A1, and the impact strength measured by a pendulum film impact tester after the polyester shrinkage film is shrunk by 10% in warm water at 80°C is set to A2, the value represented by A2 / A1×100 is a value in the range of 60 to 110%.

[0088] The reason is that by making the numerical value represented by A2 / A1×100 within the prescribed range, even if the value of the impact strength of the component (a) etc. slightly varies, the elements of the prescribed influencing factor can be reduced, and good impact strength and a prescribed ratio can be obtained in the polyester shrink film.

[0089] More specifically, if the value represented by A2 / A1×100 is less than 60% or greater than 110%, the shrinkage rate (B1, B2) of the polyester shrinkage film may vary greatly, making it difficult to obtain a stable and uniform shrinkage rate near a shrinkage temperature of 80 to 90°C.

[0090] Therefore, as for the structure (b), the numerical value represented by A2 / A1×100 is more preferably a value in the range of 65 to 105%, and further preferably a value in the range of 68 to 100%.

[0091] Furthermore, in order to more reliably control the numerical value represented by A2 / A1×100 within a predetermined range, the impact strength A2 measured by a pendulum film impact tester after shrinking the polyester shrink film by 10% in warm water at 80°C is preferably a value within the range of 20 to 45 J / mm, more preferably a value within the range of 23 to 40 J / mm, and still more preferably a value within the range of 25 to 38 J / mm.

[0092] Here, Figure 6 and Figure 7 4 and 5 show the relationship between the value of A2 / A1×100 and the shrinkage ratio (B1, B2) of the polyester shrinkage film heated under predetermined conditions.

[0093] Moreover, about Figure 6 The deviation of the measured data shown in can be understood as the existence of a corresponding correlation (in the linear approximation, the correlation coefficient (R) is 0.57) between the value of A2 / A1×100 and the shrinkage rate (B1) of the polyester shrinkage film subjected to heat treatment at 80°C for 10 seconds.

[0094] Likewise, about Figure 7 The deviation of the measured data shown in can be understood as the existence of a corresponding correlation (in the linear approximation, the correlation coefficient (R) is 0.54) between the value of A2 / A1×100 and the shrinkage rate (B2) of the polyester shrinkage film heated at 90°C for 10 seconds.

[0095] 4. Composition (c)

[0096] Constitution (c) is a necessary constituent element, and its main point is that for the polyester shrink film of the first embodiment, when the shrinkage ratio when shrinking at 80°C and 10 seconds is set to B1, and the shrinkage ratio when shrinking at 90°C and 10 seconds is set to B2, the value represented by B1 / B2×100 is a value in the range of 70 to 90%.

[0097] The reason is that by making the numerical value represented by B1 / B2×100 within the prescribed range, even if there is a slight deviation in the impact strength values ​​of composition (a) and composition (b), the elements of the prescribed influencing factors can be reduced and a stable and uniform shrinkage rate can be obtained near the shrinkage temperature of the polyester shrinkage film.

[0098] More specifically, if the value represented by B1 / B2×100 is less than 70% or greater than 90%, the shrinkage rates may vary greatly, making it difficult to obtain a stable and uniform shrinkage rate near the shrinkage temperature.

[0099] Therefore, as for the structure (c), the numerical value represented by B1 / B2×100 is more preferably a value in the range of 72 to 88%, and further preferably a value in the range of 75 to 86%.

[0100] Here, Figure 8 (a) Figure 8 (b) shows the relationship between the numerical value represented by B1 / B2×100 and the numerical value of A2 / A1×100.

[0101] Thus, if the value of A2 / A1×100 is less than 60%, the variation of the value represented by B1 / B2×100 may become large.

[0102] In addition, when the value of A2 / A1×100 is larger than 110%, there is a tendency that the deviation of the value represented by B1 / B2×100 becomes slightly larger.

[0103] Therefore, it is considered effective to make the value of A2 / A1×100 within the range of 60 to 110% in order to make the value represented by B1 / B2×100 uniform and stable.

[0104] Therefore, in order to make the numerical value represented by B1 / B2×100 more uniform and stable, it can be said that the numerical value of A2 / A1×100 is preferably within the range of 62 to 108%, and more preferably within the range of 65 to 105%.

[0105] 5. Optional elements

[0106] (1) Composition (d)

[0107] The component (d) is an optional component, and its essence is that the impact strength (A2) measured by a pendulum film impact tester when the polyester shrink film shrinks 10% in hot water at 80°C is a value within the range of 20 to 45 J / mm.

[0108] The reason for this is that by specifically limiting A2 in this way, it is easy to control the numerical value represented by A2 / A1×100 to a value within a predetermined range.

[0109] More specifically, if the impact strength A2 is less than 20 J / mm, the high-speed automatic packaging suitability and printing suitability may be poor, or damage may be easily caused by air vents caused by an automatic packaging machine.

[0110] On the other hand, if the impact strength A2 is a value exceeding 45 J / mm, it may be difficult to obtain a stable and uniform shrinkage rate near the shrinkage temperature.

[0111] Therefore, as the configuration (d), the impact strength A2 is more preferably a value within the range of 23 to 43 J / mm, and even more preferably a value within the range of 25 to 40 J / mm.

[0112] (2) Composition (e)

[0113] In addition, configuration (e) is an arbitrary configuration requirement, and its main point is that: for the polyester shrink film of the first embodiment, the shrinkage rate when shrinking under the conditions of 80°C and 10 seconds, that is, B1, is a value in the range of 35 to 80%, and the shrinkage rate when shrinking under the conditions of 90°C and 10 seconds, that is, B2, is a value in the range of 40 to 85%.

[0114] The reason for this is that by specifically limiting each of B1 and B2, it is easy to control the numerical value represented by B1 / B2×100 to a value within a predetermined range.

[0115] In other words, if the shrinkage ratio B1 is less than 35% or greater than 80%, it may be difficult to control the numerical value represented by B1 / B2×100 to a value within a predetermined range.

[0116] On the other hand, if the shrinkage ratio B2 is less than 40% or greater than 85%, when the label is attached to a PET bottle as a decorative label, the label may not be firmly attached to the bottle and a gap may be formed.

[0117] In addition, this is because it may be difficult to control the numerical value represented by B1 / B2×100 to a value within a predetermined range.

[0118] Therefore, in the configuration (e), the shrinkage ratio B1 is more preferably a value within the range of 40 to 75%, and the shrinkage ratio B2 is more preferably a value within the range of 45 to 80%.

[0119] Moreover, as a structure (e), the shrinkage ratio B1 is more preferably a value within the range of 45 to 70%, and the shrinkage ratio B2 is more preferably a value within the range of 50 to 75%.

[0120] It should be noted that for the polyester shrink film, it is preferred that the shrinkage ratio B1 when shrinking at 80°C for 10 seconds and the shrinkage ratio B2 when shrinking at 90°C for 10 seconds are respectively adjusted to values ​​within a prescribed range, and the value represented by B1 / B2×100 is limited to a value within the prescribed range.

[0121] More specifically, the numerical value represented by B1 / B2×100 is preferably a value in the range of 70 to 90%, more preferably a value in the range of 72 to 88%, and still more preferably a value in the range of 75 to 86%.

[0122] The reason for this is that the shrinkage rate of the polyester shrink film near the shrinkage temperature can be further restricted, the temperature responsiveness during shrinkage can be improved, and the yield rate of decorative labels for PET bottles and the like can be improved.

[0123] (3) Composition (f)

[0124] The configuration (f) is an optional configuration requirement, and its gist is that the film thickness before shrinkage of the polyester shrink film of the first embodiment is a value within the range of 10 to 100 μm.

[0125] The reason for this is that by specifically limiting the film thickness before shrinkage to a value within a predetermined range in this way, it is easier to control the numerical value represented by A2 / A1×100, the numerical value represented by B1 / B2×100, etc., to values ​​within predetermined ranges.

[0126] More specifically, if the film thickness before shrinkage is less than 10 μm or greater than 100 μm, it is sometimes difficult to adjust the shrinkage rate and impact strength separately, and it is also difficult to accurately adjust the value represented by A2 / A1×100, the value represented by B1 / B2×100, etc.

[0127] Therefore, as for the configuration (f), the film thickness before shrinkage is more preferably a value within the range of 10 to 100 μm, and further preferably a value within the range of 25 to 40 μm.

[0128] (4) Composition (g)

[0129] The configuration (g) is an optional configuration requirement, and its gist is that the stretch ratio in the MD direction of the polyester shrink film of the first embodiment before shrinkage is a value within a range of 100 to 200%.

[0130] The reason for this is that by specifically limiting the stretch ratio in the MD direction of the film before shrinkage to a value within a specified range, it is easy to more easily and quantitatively control the numerical value represented by A2 / A1×100, the numerical value represented by B1 / B2×100, etc. to a value within a specified range.

[0131] More specifically, this is because if the stretch ratio in the MD direction of the film before shrinkage is a value less than 100%, the production yield may be significantly reduced.

[0132] On the other hand, if the stretching ratio in the MD direction exceeds 200%, the shrinkage rate in the TD direction may be affected, making it difficult to adjust the shrinkage rate itself.

[0133] Therefore, as for the configuration (g), the stretch ratio in the MD direction of the film before shrinkage is more preferably a value within the range of 110 to 180%, and even more preferably a value within the range of 120 to 170%.

[0134] (5) Composition (h)

[0135] The configuration (h) is an optional configuration requirement, and its gist is that the stretch ratio in the TD direction of the polyester shrink film of the first embodiment before shrinkage is a value within the range of 300 to 600%.

[0136] The reason for this is that by limiting not only the stretching ratio in the MD direction of the film before shrinkage but also the stretching ratio in the TD direction to values ​​within the specified range, it is easy to more easily and quantitatively control the numerical value represented by A2 / A1×100, the numerical value represented by B1 / B2×100, etc. to values ​​within the specified range.

[0137] More specifically, if the stretch ratio in the TD direction of the film before shrinkage is less than 300%, the shrinkage ratio in the TD direction may be significantly reduced, which may excessively limit the use of the polyester shrink film.

[0138] On the other hand, if the stretch ratio in the TD direction of the film before shrinkage is greater than 600%, the shrinkage ratio may become significantly large, which may excessively limit the use of the polyester shrink film or make it difficult to control the stretch ratio itself constantly.

[0139] Therefore, as the configuration (h), the stretch ratio in the TD direction of the film before shrinkage is more preferably a value within the range of 350 to 550%, and even more preferably a value within the range of 400 to 500%.

[0140] (6) Composition (i)

[0141] The configuration (i) is an optional configuration requirement, and its gist is that the polyester shrink film of the first embodiment has a haze value measured in accordance with JIS K 7105 of the film before shrinkage of 5% or less.

[0142] The reason for this is that by specifically limiting the haze value to a value within a predetermined range, it is easy to quantitatively control the transparency of the polyester shrink film.

[0143] More specifically, if the haze value of the film before shrinkage is greater than 5%, the transparency may decrease, making it difficult to use the film for decorative purposes on PET bottles.

[0144] On the other hand, if the haze value of the film before shrinkage is excessively small, it may be difficult to stably control the haze value, and the production yield may be significantly reduced.

[0145] Therefore, as for the configuration (i), the haze value of the film before shrinkage is more preferably a value within the range of 0.1 to 3%, and even more preferably a value within the range of 0.5 to 1%.

[0146] (7) Composition (j)

[0147] The configuration (j) is an optional configuration requirement, and its gist is that the polyester shrink film of the first embodiment contains 90 to 100% by weight of the total amount of the amorphous polyester resin.

[0148] The reason for this is that by limiting the content of the amorphous polyester resin to a value within a specified range, even when the impact strength values ​​of components (a) and (b) slightly differ, the blending amount can be appropriately adjusted to reduce the factors affecting the specified range.

[0149] Therefore, as a result, the impact strength and the shrinkage rate near the shrinkage temperature of the polyester shrinkage film can be adjusted to a desired range, and the haze value and the like can also be easily controlled quantitatively.

[0150] More specifically, if the content of the amorphous polyester resin is less than 90%, it may be difficult to control the impact strength of the polyester shrinkage film and the shrinkage rate near the shrinkage temperature.

[0151] However, if the content of the amorphous polyester resin is too large, there is a possibility that the range of factors for reducing the prescribed influencing factors will be significantly narrowed.

[0152] Therefore, as the component (j), the content of the amorphous polyester resin is more preferably within a range of 90 to 100% by weight of the total amount, and further preferably within a range of 91 to 100% by weight.

[0153] (8) Others

[0154] It is preferred that various additives are compounded or attached to the polyester shrink film of the first embodiment on one side or both sides thereof.

[0155] More specifically, at least one of an anti-hydrolysis agent, an antistatic agent, an ultraviolet absorber, an infrared absorber, a colorant, an organic filler, an inorganic filler, an organic fiber, an inorganic fiber, etc. is preferably blended in an amount of 0.01 to 10% by weight, more preferably 0.1 to 1% by weight, based on the total amount of the polyester shrink film.

[0156] In addition, if Figure 1 As shown in (b) in FIG. 1 , it is also preferred that other resin layers 10 a and 10 b containing at least one of these various additives be laminated on one or both surfaces of the polyester shrink film 10 .

[0157] At this time, when the thickness of the polyester shrink film is defined as 100%, the single layer thickness or the total thickness of the other resin layers to be laminated is usually preferably a value within a range of 0.1 to 10%.

[0158] The resin as the main component constituting the other resin layer may be the same polyester resin as the polyester shrink film, or at least one of acrylic resins, olefin resins, polyurethane resins, rubber resins, etc. different therefrom.

[0159] In addition, it is also preferred to make the polyester shrink film into a multilayer structure to further achieve anti-hydrolysis effect and mechanical protection, or Figure 1 As shown in (c) in FIG. 1 , a shrinkage ratio adjusting layer 10 c is provided on the surface of the polyester shrinkage film 10 so that the shrinkage ratio of the polyester shrinkage film becomes uniform in the surface.

[0160] The shrinkage ratio adjusting layer can be laminated by using an adhesive, a coating method, or a heat treatment according to the shrinkage characteristics of the polyester shrinkage film.

[0161] More specifically, when the thickness of the shrinkage ratio adjusting layer is in the range of 0.1 to 3 μm and the shrinkage ratio of the polyester shrinkage film at a predetermined temperature is too large, it is preferred to laminate a shrinkage ratio adjusting layer of a type that suppresses the shrinkage ratio.

[0162] When the shrinkage rate of the polyester shrinkage film at a predetermined temperature is too small, it is preferable to laminate a shrinkage rate adjusting layer of a type that increases the shrinkage rate.

[0163] Thereby, as a polyester-based shrinkage film, various shrinkage films having different shrinkage ratios are not produced, but a desired shrinkage ratio can be obtained by the shrinkage ratio adjusting layer.

[0164] [Second embodiment]

[0165] The second embodiment is an embodiment related to the method for producing the polyester shrink film of the first embodiment.

[0166] 1. Raw material preparation and mixing process

[0167] First, as raw materials, it is preferable to prepare a non-crystalline polyester resin, a crystalline polyester resin, a rubber-based resin, a main agent such as an antistatic agent and an anti-hydrolysis agent, and additives.

[0168] Next, the prepared crystalline polyester resin, amorphous polyester resin, etc. are preferably added while weighing into a stirring container, and mixed and stirred until uniform using a stirring device.

[0169] 2. Production process of blanks

[0170] Next, the uniformly mixed raw materials are preferably dried to an absolutely dry state.

[0171] Next, extrusion molding is typically preferably performed to produce a green sheet having a predetermined thickness.

[0172] More specifically, for example, extrusion molding can be performed at an extrusion temperature of 180° C. using an extruder having an L / D of 24 and an extrusion screw diameter of 50 mm (manufactured by TANABE PLASTICS CO., LTD.) to obtain a green sheet having a predetermined thickness (usually 10 to 100 μm).

[0173] 3. Production of polyester shrink film

[0174] Next, the obtained green sheet is heated and pressed while being moved on or between rolls using a shrink film production apparatus to produce a polyester shrink film.

[0175] That is, it is preferred that the polyester molecules constituting the polyester shrink film be crystallized into a predetermined shape by heating and pressing the film while substantially widening the film width at a predetermined stretching temperature and stretching ratio, and stretching the film in a predetermined direction.

[0176] Then, by curing the film in this state, a heat-shrinkable polyester shrink film for use as a decoration, a label, etc. can be produced.

[0177] 4. Inspection process of polyester shrink film

[0178] It is preferred that the following properties and the like be measured continuously or intermittently for the produced polyester shrink film, and a predetermined inspection step be provided.

[0179] That is, by measuring the following characteristics and the like in a predetermined inspection process and confirming that the values ​​fall within a predetermined range, a polyester shrink film having more uniform shrinkage characteristics and the like can be obtained.

[0180] 1) Visual inspection of polyester shrink film

[0181] 2) Thickness unevenness measurement

[0182] 3) Determination of tensile elastic modulus

[0183] 4) Tear strength measurement

[0184] 5) Determination of viscoelastic properties based on SS curve

[0185] Then, it can be said that it is preferable to further add the following measurements (a) to (c) in the production of the polyester shrink film of the second embodiment.

[0186] (a) Impact strength A1 before shrinkage measured by a pendulum film impact tester.

[0187] (b) A2 is a value represented by A2 / A1×100, where A2 is the impact strength measured by a pendulum film impact tester after shrinking the polyester shrink film by 10% in hot water at 80°C.

[0188] (c) The value represented by B1 / B2×100, where B1 is the shrinkage ratio when the polyester shrink film is shrunk at 80°C for 10 seconds and B2 is the shrinkage ratio when the polyester shrink film is shrunk at 90°C for 10 seconds.

[0189] [Third Embodiment]

[0190] The third embodiment is an embodiment related to a method of using a polyester-based shrink film.

[0191] Therefore, any known method of using a shrink film can be suitably applied.

[0192] For example, when implementing the method of using a polyester shrink film, first, the polyester shrink film is cut into appropriate length and width and formed into a long tube.

[0193] Next, the long tube is fed to an automatic labeling device (shrink labeler) and further cut into required lengths.

[0194] Next, it is externally fitted on a PET bottle or the like filled with the content.

[0195] Next, as a heat treatment for the polyester shrink film to be externally fitted on a PET bottle or the like, the film is passed through a hot air duct or a steam duct at a predetermined temperature.

[0196] Then, radiant heat such as infrared rays or heating steam at about 90° C. provided in these passages is blown from the surroundings, thereby uniformly heating and heat-shrinking the polyester shrink film.

[0197] This allows the container to be brought into close contact with the outer surface of a PET bottle or the like, and a labeled container can be quickly obtained.

[0198] Here, according to the polyester shrink film of the present invention, by satisfying at least the components (a) to (b), even when the impact strength value of the component (a) slightly varies, the elements that affect the predetermined factors can be reduced and appropriate impact strength can be obtained in the polyester shrink film.

[0199] Therefore, as described below, good results can be obtained in a predetermined drop test.

[0200] Furthermore, by satisfying configuration (c), even when the impact strength values ​​of configurations (a) and (b) slightly vary, it is possible to reduce the factors affecting the predetermined factors and obtain stable and uniform shrinkage properties near the shrinkage temperature of the polyester shrink film.

[0201] Furthermore, since the polyester shrink film of the present invention contains substantially no structural unit derived from lactic acid, it also has an advantage that strict humidity management under storage conditions is not required.

[0202] Example

[0203] Hereinafter, the present invention will be described in detail based on examples. However, the scope of rights of the present invention is not limited by the description of the examples unless there is a particular reason.

[0204] In addition, in the examples, the resins used are as follows.

[0205] (PETG1)

[0206] Amorphous polyester composed of dicarboxylic acid: 100 mol% terephthalic acid and diols: 70 mol% ethylene glycol, 25 mol% 1,4-cyclohexanedimethanol, and 5 mol% diethylene glycol

[0207] (PETG2)

[0208] Amorphous polyester composed of dicarboxylic acid: 100 mol% terephthalic acid and diols: 72 mol% ethylene glycol, 25 mol% neopentyl glycol, and 3 mol% diethylene glycol

[0209] (APET)

[0210] Crystalline polyester composed of dicarboxylic acid: 100 mol% terephthalic acid and diol: 100 mol% ethylene glycol

[0211] (PBT)

[0212] Crystalline polyester composed of dicarboxylic acid: 100 mol% terephthalic acid and diol: 1,4-butanediol 100 mol%

[0213] [Example 1]

[0214] 1. Production of polyester shrink film

[0215] 100 parts by weight of amorphous polyester resin (PETG1) was used in a stirring container.

[0216] Next, the raw material was brought to an absolute dry state and then extruded at an extrusion temperature of 180° C. using an extruder having a L / D of 24 and an extrusion screw diameter of 50 mm (manufactured by TANABE PLASTICS CO., LTD.) to obtain a green sheet having a thickness of 100 μm.

[0217] Next, a polyester shrink film having a thickness of 30 μm was produced from the green sheet using a shrink film production apparatus at a stretching temperature of 83° C. and a stretching ratio (MD direction: 105%, TD direction: 480%).

[0218] 2. Evaluation of polyester shrink film

[0219] (1) Thickness

[0220] The thickness of the obtained polyester shrink film (using a desired value of 30 μm as a reference value) was measured using a micrometer and evaluated based on the following criteria.

[0221] ⊚: The thickness deviation is a value within the range of ±0.1 μm of the reference value.

[0222] ○: The thickness deviation is a value within the range of ±0.5 μm of the reference value.

[0223] △: The thickness deviation is a value within the range of ±1.0 μm from the reference value.

[0224] ×: The thickness deviation is a value within the range of ±3.0 μm from the reference value.

[0225] (2) Impact strength 1

[0226] The impact strength (J / mm, A1) of the polyester shrink film before shrinkage was measured in accordance with ASTM-D3420 using a TSS film impact tester (manufactured by Toyo Seiki Seisaku-sho) whose pendulum tip was a semi-spherical ball, and evaluated based on the following criteria.

[0227] ◎: Values ​​within the range of 25 to 40 J / mm.

[0228] ○: A value within the range of 23 to 50 J / mm and a value outside the range of 25 to 40 J / mm.

[0229] △: A value within the range of 20 to 60 J / mm and a value outside the range of 23 to 50 J / mm.

[0230] ×: Out of the range of 20 to 60 J / mm.

[0231] (3) Impact strength 2

[0232] The impact strength (J / mm, A2) of the polyester shrink film after shrinking by 10% in hot water at 80°C was measured in the same manner as in the measurement of the impact strength 1, and evaluated based on the following criteria.

[0233] ◎: Values ​​within the range of 25 to 38 J / mm.

[0234] ○: A value within the range of 23 to 40 J / mm and a value outside the range of 25 to 38 J / mm.

[0235] △: A value within the range of 20 to 45 J / mm and a value outside the range of 23 to 40 J / mm.

[0236] ×: Out of the range of 20 to 45 J / mm.

[0237] (4) Impact strength 3

[0238] A2 / A1×100 was calculated from the impact strength (A2 / A1) of the polyester shrink film before and after shrinkage, and the evaluation was performed based on the following criteria.

[0239] ◎: A value within the range of 65 to 105%.

[0240] ○: A value within the range of 60 to 110% and outside the range of 65 to 105%.

[0241] △: The value is within the range of 50 to 120% and is outside the range of 60 to 110%.

[0242] ×: A value outside the range of 50 to 120%.

[0243] (5) Shrinkage rate 1

[0244] The obtained polyester shrink film (TD direction) was immersed in warm water at 80° C. for 10 seconds using a thermostatic bath (B1 condition) to be heat-shrunk.

[0245] Next, the shrinkage ratio (B1) was calculated based on the following formula from the dimensional changes before and after the respective heat treatments, and was evaluated based on the following criteria.

[0246] Shrinkage ratio = (length of film before heat shrinkage - length of film after heat shrinkage) / length of film before heat shrinkage × 100

[0247] ⊚: The shrinkage ratio (B1) is a value within the range of 35 to 80%.

[0248] ○: The shrinkage ratio (B1) is a value within the range of 30 to 85% and a value outside the range of 35 to 80%.

[0249] △: The shrinkage ratio (B1) is a value within the range of 25 to 90% and a value outside the range of 30 to 85%.

[0250] ×: The shrinkage ratio (B1) is a value outside the range of 25 to 90%.

[0251] (6) Shrinkage rate 2

[0252] The obtained polyester shrink film (TD direction) was immersed in warm water at 90° C. for 10 seconds using a thermostatic bath (B2 condition) to be heat-shrunk.

[0253] Next, the shrinkage ratio (B2) was calculated based on the following formula from the dimensional changes before and after the respective heat treatments, and was evaluated based on the following criteria.

[0254] Shrinkage ratio = (length of film before heat shrinkage - length of film after heat shrinkage) / length of film before heat shrinkage × 100

[0255] ⊚: The shrinkage ratio (B2) is a value within the range of 50 to 75%.

[0256] ○: The shrinkage ratio (B2) is a value within the range of 45 to 80% and a value outside the range of 50 to 75%.

[0257] △: The shrinkage ratio (B2) is a value within the range of 40 to 85% and a value outside the range of 45 to 80%.

[0258] ×: The shrinkage ratio (B2) is a value outside the range of 40 to 85%.

[0259] (7) Shrinkage rate 3

[0260] B1 / B2×100 was calculated from the shrinkage ratio (B1 and B2 in the TD direction) of the obtained polyester shrinkage film, and the evaluation was performed based on the following criteria.

[0261] ⊚: The shrinkage ratio 3 is a value within the range of 75 to 85%.

[0262] ○: The shrinkage ratio 3 is a value within the range of 70 to 90% and a value outside the range of 75 to 85%.

[0263] △: The shrinkage ratio 3 is a value within the range of 65 to 98% and a value outside the range of 70 to 90%.

[0264] ×: The shrinkage ratio 3 is a value outside the range of 65 to 98%.

[0265] (8) Haze

[0266] The haze value of the obtained polyester shrink film was measured based on JIS K 7105 and evaluated based on the following criteria.

[0267] ◎: A value of 1% or less.

[0268] ○: A value of 3% or less.

[0269] △: A value of 5% or less.

[0270] ×: A value larger than 5%.

[0271] (9) Drop test

[0272] A commercially available cylindrical PET bottle (trade name: evian, volume: 500 ml) filled with drinking water was prepared.

[0273] Next, a polyester shrink film was cut into a strip with a width of 26 cm to form a 1 mm wide perforation along the longitudinal direction, 1,3-dioxolane was applied to the ends in the width direction, and the ends in the width direction were overlapped and bonded to each other so that the overlapped edge was about 1 cm, to form a tubular film with a diameter of about 8 cm. The tubular film was further cut every 5 cm in the longitudinal direction to obtain a plurality of tubular labels.

[0274] Next, the tubular label was placed on the prepared cylindrical PET bottle, which was placed on a conveyor and moved at a speed of 6 m / min in a steam tunnel maintained at 85° C. to heat-shrink the tubular label and adhere to the cylindrical PET bottle.

[0275] Next, the label-shaped polyester shrink film was torn to open the holes so that the remaining width of the label would be one hole remaining, thereby preparing a sample for a drop test.

[0276] Next, the drop test sample was naturally dropped from a height of 1.5 m on a concrete floor, and the number of times the label-shaped polyester shrink film was broken or damaged was measured by visual observation. The drop test performance was evaluated according to the following criteria.

[0277] ◎: Can withstand more than 3 drop tests.

[0278] ○: Can withstand more than 2 drop tests.

[0279] △: Can withstand one drop test.

[0280] ×: Unable to withstand one drop test.

[0281] [Examples 2 to 9]

[0282] In Examples 2 to 9, the values ​​of the components (a) to (c) and the like were changed as shown in Tables 1 and 2, respectively, and polyester shrink films were produced and evaluated in the same manner as in Example 1.

[0283] That is, in Example 2, the evaluation was carried out in the same manner as in Example 1 except that the amorphous polyester resin (PETG1) was used as the raw material and the extrusion conditions were changed to produce a polyester shrink film having a thickness of 25 μm.

[0284] In Example 3, the evaluation was carried out in the same manner as in Example 1 except that an amorphous polyester resin (PETG1) was used as a raw material and the extrusion conditions were changed to produce a polyester shrink film having a thickness of 30 μm.

[0285] In Example 4, 90 parts by weight of amorphous polyester resin (PETG1) and 10 parts by weight of crystalline polyester resin (APET) were mixed as raw materials, and extrusion conditions were changed to produce a polyester shrink film with a thickness of 30 μm. The evaluation was carried out in the same manner as in Example 1, except that the mixture was used as raw materials and the extrusion conditions were changed.

[0286] In Example 5, 90 parts by weight of amorphous polyester resin (PETG1) and 10 parts by weight of crystalline polyester resin (PBT) were mixed as raw materials, and extrusion conditions were changed to produce a polyester shrink film having a thickness of 25 μm. The evaluation was carried out in the same manner as in Example 1, except that the mixture was used as raw materials and the extrusion conditions were changed.

[0287] In Example 6, the evaluation was carried out in the same manner as in Example 1 except that only the amorphous polyester resin (PETG2) was used as the raw material and the extrusion conditions were changed to produce a polyester shrink film having a thickness of 40 μm.

[0288] In Example 7, the evaluation was carried out in the same manner as in Example 1 except that only the amorphous polyester resin (PETG2) was used as the raw material and the extrusion conditions were changed to produce a polyester shrink film having a thickness of 39 μm.

[0289] In Example 8, the evaluation was carried out in the same manner as in Example 1 except that only the amorphous polyester resin (PETG2) was used as the raw material and the extrusion conditions were changed to produce a polyester shrink film having a thickness of 21 μm.

[0290] In Example 9, the evaluation was carried out in the same manner as in Example 1 except that only the amorphous polyester resin (PETG2) was used as the raw material and the extrusion conditions were changed to produce a polyester shrink film having a thickness of 22 μm.

[0291] [Comparative Example 1]

[0292] In Comparative Example 1, as shown in Tables 1 and 2, a polyester shrink film that did not satisfy the constituent requirement (b) was prepared, and the same evaluation as in Example 1 was carried out.

[0293] That is, a polyester shrink film having a thickness of 25 μm and not satisfying the constituent requirement (b) was produced using only the same amorphous polyester resin (PETG1) as in Example 1 as a raw material.

[0294] [Comparative Example 2]

[0295] In Comparative Example 2, as shown in Tables 1 and 2, a polyester shrink film that did not satisfy the constituent requirements (b) and (c) was prepared, and the polyester shrink film was prepared and evaluated in the same manner as in Example 1.

[0296] That is, a polyester shrink film having a thickness of 29 μm and not satisfying the constituent requirements (b) and (c) was produced using only the amorphous polyester resin (PETG2) as a raw material.

[0297] [Table 1]

[0298]

[0299] [Table 2]

[0300] Stretching temperature(℃) Heat fixation temperature (℃) MD stretch ratio (%) TD stretch ratio (%) Example 1 83 81 105 480 Example 2 84 82 125 480 Example 3 76 73 105 460 Example 4 83 82 100 500 Example 5 81 80 125 480 Example 6 88 85 120 450 Example 7 80 75 105 480 Example 8 90 85 200 350 Example 9 90 85 180 350 Comparative Example 1 86 85 111 500 Comparative Example 2 75 73 105 480

[0301]

[0302] Industrial Applicability

[0303] According to the present invention, the disadvantages of conventional polyolefin-based shrink films and polyester-based shrink films containing structural units obtained by dehydration condensation of lactic acid can be eliminated, and a polyester-based shrink film having excellent impact resistance and a uniform shrinkage rate near the shrinkage temperature can be provided.

Claims

1. A polyester shrink film, which is a single-layer polyester shrink film having the following structures (a) to (c), (a) The impact strength before shrinkage measured by a pendulum film impact tester is defined as A1, and this A1 is a value within a range of 20 to 60 J / mm, (b) when the impact strength measured by a pendulum film impact tester after shrinking the polyester shrink film by 10% in warm water at 80°C is defined as A2, the value represented by A2 / A1×100 in relation to A1 is within the range of 60 to 110%, (c) when the shrinkage ratio of the polyester shrink film when it is shrunk in hot water at 80° C. for 10 seconds is defined as B1, and when the shrinkage ratio of the polyester shrink film when it is shrunk in hot water at 90° C. for 10 seconds is defined as B2, the value represented by B1 / B2×100 is a value within the range of 70 to 90%, The non-crystalline polyester is contained in an amount of 90 to 100% by weight of the total amount of the resin.

2. The polyester shrink film according to claim 1, characterized in that: The impact resistance A2 is a value within a range of 20 to 45 J / mm.

3. The polyester shrink film according to claim 1 or 2, characterized in that: The shrinkage ratio B1 is a value within a range of 35 to 80%, and the shrinkage ratio B2 is a value within a range of 40 to 85%.

4. The polyester shrink film according to claim 1 or 2, characterized in that: The film thickness before shrinkage is a value within a range of 10 to 100 μm.

5. The polyester shrink film according to claim 1 or 2, characterized in that: The stretching ratio in the MD direction of the film before shrinkage is a value within a range of 100 to 200%.

6. The polyester shrink film according to claim 1 or 2, characterized in that: The stretching ratio in the TD direction of the film before shrinkage is a value within a range of 300 to 600%.

7. The polyester shrink film according to claim 1 or 2, characterized in that: The haze value of the film before shrinkage measured in accordance with JIS K7105 is 5% or less.

8. The polyester shrink film according to claim 1 or 2, characterized in that: The amorphous polyester is composed of dicarboxylic acid and diol, wherein at least 80 mol % of the dicarboxylic acid is composed of terephthalic acid, and the diol is composed of 50 to 80 mol % of ethylene glycol and 20 to 50 mol % of one or more diols selected from 1,4-cyclohexanedimethanol, neopentyl glycol and diethylene glycol.

Citation Information

Patent Citations

  • Polyolefin-based thin film multilayered shrink film

    JP2011126247A

  • Laminated polyester film for molding and its manufacturing process

    CN101484317A

  • Heat-shrinkable white polyester film, process for producing heat-shrinkable white polyester film, label, and package

    CN101970212A